A VLT/X-Shooter study of accretion and photoevaporation in Transitional Disks. Issue Volume 8:Issue S299(2013) (6th January 2014) - Manara, C. F.; Testi, L.; Natta, A.; Ricci, L.; Benisty, M.; Rosotti, G.; Ercolano, B.
Abstract: We present preliminary results of a detailed study of the accretion, stellar, and wind properties of transitional disks (TDs) carried out with the X-Shooter spectrograph. Combining new and archival spectra, we collected a sample of more than 20 TDs from different nearby star-forming regions. Our sample includes objects with both small (<5-15 AU) and large (>20–30 AU) known inner hole size from the literature (either from mm-observations or IR SED fitting). We check their stellar parameters (Teff, L*, A V, M * ) and derive their accretion properties (Lacc, Ṁ acc ) in a self-consistent way, which makes use of the wide wavelength coverage of X-Shooter, and study their wind properties by mean of different forbidden emission lines analysis.